The effect of methanol flow rate and repeated use on amberlyst catalyst characteristics in palm fatty acid distillate (PFAD) esterification reaction - Dian Wardana; Eddiyanto Eddiyanto; Nurfajriani Nurfajriani; Saharman Gea (Pascasarjana Universitas Negeri Medan, 2023)
Palm fatty acid distillate (PFAD) is a waste from cooking oil which is rich in free fatty acids (FFA). The high FFA content in PFAD allows PFAD to be processed into a renewable and economically valuable energy source, namely biodiesel through an esterification process using methanol with the help of an amberlyst catalyst. This study aims to see how the effect of variations in flow rates on the conversion of PFAD to biodiesel which takes place in a continuous reactor and to see the effect of repeated use of catalysts at optimum conditions on the conversion rate. The results showed that the optimum conditions were obtained with a methanol flow rate of 2 ml/minute. The flow rate of methanol above 2 ml/minute actually inhibits the reaction process. The repeated use of the catalyst reduces the availability of active sites and increases the presence of impurities and reduces the thermal stability of the catalyst at high temperatures.Keywords: Amberlist; Biodiesel; Esterification; PFAD